Analysing the relationship between cognition and urine storage function. Issue 2 (27th February 2019) - Koitabashi, Rika; Uchida, Yoko
Abstract : Is the urine storage function associated with cognitive function? With ageing, overactive bladder syndrome (OAB) can develop. OAB is causally related to dementia. However, the relationship between cognitive function and urine storage function has not been analysed. The purpose of this study was to examine this relationship. It has been reported that dementia is associated with both OAB and functional incontinence, cognitive function declines in individuals taking an oral anticholinergic drug for OAB. Dementia is therefore closely associated with urine storage function. However, there are as yet no assessments of the relationship between cognitive function and urine storage function. This study is quantitative research. The subjects were 81 patients in a hospital or nursing home, who did not have urinary catheters or intravenous feeding, and did not receive therapeutic drugs for lower urinary tract symptoms. Consent was obtained by the explanation using the document. We evaluated cognitive function using Hasegawa's Revised Dementia Scale. We judged urine storage function from urine volume once and residual urine volume. We analysed the relationship by multiple logistic regression analysis. The analysis showed that the factor that most strongly influenced urine storage function was cognitive function; subjects with low cognitive function tended to have urine storage dysfunction. In hospitals and institutions, patients with decreased cognitive function may demonstrate early urine storage dysfunction. This must be considered when providing urinary care.